Metody vzdělávání manažerů a jejich hodnocení - Horčička, Aleš (Univerzita Pardubice, 2008)
The article deals with managerial education. Basic concepts related to the problems are explained and the educational process is described. An attention is also paid to the specific educational program. The aim of the article is to describe the problems from the point of view of the educational facilities, to analyze the specific training sessions, including a draft of possible innovation in training program and training day leadership (a draft of questionnaire action).
Keywords: Human Resources Management; managers eduacation; training methods; educational process; Evaluation